Cooperation and coordination in green supply chain with R&D uncertainty. Issue 3 (4th March 2022) - Yang, Feng; Kong, Junjun; Liu, Tianzhuo; Ang, Sheng
Abstract: Considering the uncertainty of environmental R&D, we investigate a two-echelon supply chain consisting of a manufacturer who invests in green manufacturing to generate a probability of R&D success and a retailer who exerts green marketing to disclose information on the successful R&D outcome to consumers. We explore cooperation issues in green operations by analysing two modes: Decentralized mode where the two firms do not cooperate in green operations, and Cartelization mode where they cooperate as an integrated system to set their individual green decision. We find Cartelization mode increases the profitability for the whole supply chain and the manufacturer but not the retailer. Compared with Decentralized mode, the green supply chain in Cartelization mode cannot be Pareto-improved unless the manufacturer efficiently motivates the retailer to cooperate. Furthermore, we discuss coordination issues under these two modes and find the revenue-sharing contract has more flexibility when coordinating the cartelized supply chain.